Is There a Biological Law of Human Population Growth? - Wolfe, A. B. (Quarterly Journal of Economics, 1927)
The work of Pearl and Reed, 558 — Their postulates, 559. — The logistic formula, 561. — The question of closeness of fit of the formula to the observed data, 562. — The applications of a mathematical formula of growth, 564. — Intercensal interpolation, 564. — Prediction of future growth, 566. — Malthus, 568. — Elkanah Watson, 569. — Department of Agriculture experts, 570. — Pritchett, 571. — Critique of Pearl's assumptions and of his formula as a predictive device, 573. — Cultural influences and cycles of growth, 577. — Empirical versus rational laws, 579. — The use and abuse of analogy, 582. — The analogy between the growth of an individual and that of an aggregate, 583. — Relation of changing birth rates, death rates, and age constitution to the shape of the growth curve, 586. — The Algerian population, 587. — Inconclusiveness of Pearl's analysis, 589. — Further analogy — correlation of population growth with density, 590. — Doubtful value of the logistic formula, 593.